Procalcific effect of proprotein convertase subtilisin/kexin type 9 (PCSK9) in chronic kidney disease (CKD). (25th November 2020) - Ferri, N; Lupo, M.G.P; Rattazzi, M.R
Abstract: Aim: PCSK9 has been recently associated with a higher rate of calcification in hypercholesterolemic, diabetes and CKD patients. The aim of this study was thus to investigate the role of PCSK9 in VC process, under uremic condition, both on in vivo and in vitro experimental settings. Methods: Sprauge Dawley rats were fed a standard diet (SD, n=11) or uremic diet (UD, n=11) for 6 weeks. Calcium crystals in aortas were visualized by von Kossa staining and quantified by a colorimetric assay and plasma total cholesterol determined. Control and PCSK9-overexpressing smooth muscle cells (SMCsPCSK9) were cultured with 2.5% FCS ± Pi for 7 days. Hydroxyapatite deposition by SMCs was measured by a colorimetric assay. The number and the content of pro-calcific extracellular vesicles (EVs) budding from the cells were determined. Results: The hyperphosphatemia secondary to CKD lead to rat aortic calcification (+7.3-fold) and a significant increase in TC and PCSK9 levels (+1.4 and +2.7-fold, respectively). Higher expression of PCSK9 was also observed in kidney (+4.8-fold) and liver (+1.5-fold). SMCsPCSK9 showed higher extracellular calcium deposition (+1.4-fold) in response to Pi and increase EVs production (+7-fold). The incubation of control cells with recombinant PCSK9 did not induce extracellular calcium deposition. Conclusions: Our study suggest a positive effect of intracellular PCSK9 on vascular calcification in CKD condition. Pro-calcific budding of EVs seems one of the possible mediators of this process. Funding Acknowledgement: Type of funding source: None